THE CREATION OF NEW STRUCTURES WHILE PERCEIVING A PIECE OF ART - Papucha, Mykola (PSYCHOLOGICAL JOURNAL, 2020)
The article explores the thesis that new structures are not always formed during artistic work perception, as evidenced by, in particular, our own experience. A text (any artistic work at all) can produce new structures if it is perceived and experienced as an event. The article underlines that so-called “entry” is the main operational parameter at this case. The article also describes several experimental studies involving students in non-artistic specialities and intended to evoke actual aesthetic perception (structuring) if conditions are created for “entry” and active “being” within the space of an art piece. It is summarized that all described experiments were effective even regardless of participants’ personalities and exhibited artwork; the participants demonstrated clearly enough in their narratives that their experiencing of an art piece led to formation of new structures within their inner worlds. Our own studies in art psychology domain provided us with empiric material proving that under certain conditions art works should be regarded as “structure-generating”: their perception through conceptual lenses of “entry” and “encompassing” leads to bright experiencing, and consequently creation of new structures in an individual’s inner world. The most essential factor distinguishing an artwork from a non-artwork lies within special correlation of its form and its material (content). Despite a traditional idea about their “unity” in artwork, we state that art can appear only wherein an author, using vital material, overcomes its life-form, and exactly this overcoming allows ordinary and routine everyday thing to grow into an aesthetic phenomenon. According to studies, a catharsis may happen to human being due to collision of two emotions with opposite modalities. So, the article justifies the thesis that all poetic works of V.S. Vysotsky are actual artworks and any Vysotsky’s verse potentially contains a chance of perceptual catharsis that is provided through overcoming of vital material by an artistic form. Conclusion is drawn that Vysotsky’s works can be considered as the top of poetic mastery according to their influence on an individual’s emotional sphere.